Chinese Patent Medicine Shufeng Jiedu Capsules as an Adjuvant Therapy for Community-Acquired Pneumonia: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Zhang, Xiao-Wen; Xia, Ru-Yu; Gao, Jia-Qi; Liu, Jin-Jun; Xu, De-Hao; Li, Xun; Hu, Xiao-Yang; Willcox, Merlin; Moore, Michael; Dai, Meng-Yuan; Trill, Jeanne; Fei, Yu-Tong; et al. (Frontiers in Pharmacology, 2022)
Background: Shufeng Jiedu (SFJD) capsules can be used as adjunctive treatment for patients with community-acquired pneumonia, but the effectiveness and safety of SFJD are not clear. This review aims to evaluate the effectiveness and safety of SFJD based on randomized controlled trials (RCTs). Methods: A systematic review was conducted by searching PubMed, Embase, Scopus, Web of Science, CENTRAL, CNKI, VIP, CBM, Wanfang and trial registry platforms from their inception to Mar 2022. Two reviewers screened studies, extracted the data and assessed risk of bias independently. The data were pooled for meta-analysis or presented narratively. Results: Seventeen RCTs involving 1840 participants were included. All trials compared SFJD plus antibiotics to antibiotics, or combined with symptomatic treatment in both groups. The overall certainty of evidence was assessed as moderate to very low certainty. Compared with routine treatment (antibiotics alone or antibiotics plus symptomatic treatment), SFJD plus routine treatment showed beneficial effects in resolution of fever (MD -1.20 days, 95%CI -1.73 to -0.67; 10 RCTs; very low certainty), cough (MD -1.02 days, 95%CI -1.23 to -0.81; 9 RCTs; moderate certainty), phlegm (MD -1.46 days, 95%CI -2.84 to -0.08; 6 RCTs; very low certainty), pulmonary crepitations (MD -1.61 days, 95%CI -2.64 to -0.59; 8 RCTs; low certainty), shortness of breath (MD -2.80 days, 95%CI -2.88 to -2.72; 2 RCTs; low certainty) and chest pain (MD -2.85 days, 95%CI -3.01 to -2.69; 1 RCT; low certainty). There was no significant difference in pathogen clearance (1 RCT). No serious adverse events were reported, but 2.60% (5/192) patients reported nausea in the SFJD groups, 1.04% (2/192) participants in routine group, and no significant difference was identified. Conclusions: Current evidence suggests that adding SFJD may shorten the duration of symptom relief in community-acquired pneumonia for 1-2 days. The adverse events were minor and controllable, and no serious adverse events were reported. Well-reported trials and potential of reducing antibiotics were expected in the future studies. Protocol registration: INPLASY 202060102 (doi: 10.37766/inplasy2020.6.0102)